Beta-Cyclodextrin As An Excipient In Drug Formulation - A, Bhargav (Asian Journal of Pharmaceutical Research and Development, 2021)
After its discovery nearly 30 years ago, (2-Hydroxy –propyl) Beta –Cyclodextrin, a highly soluble derivative of Beta –Cyclodextrin, has been an authorized excipients of drug formulation in both the US and European pharmacopoeia. It is recommended for use in oral and parenteral formulations as a solubilizer and stabilizer. The majority of medications taken by mouth have low aqueous solubility and dissolution rates. Beta-Cyclodextrin that has been chemically modified Dynamic complex formation used to enchance the Low aqueous solubility, slow dissolution rate, and reduced drug stability. Cyclodextrin form inclusion complexes with appropriately sized guest molecules to improve aqueous solubility, physical chemical stability, and bioavailability of drugs. Cyclodextrin is a group of compounds made up of glucose monomers arranged in a donut form. They are non-reducing, crystalline cyclic oligosaccrides with a truncated core that produces a hydrophilic outer surface. Cyclodextrin and its derivatives have become common modalities for increasing oral bio availability and absorption rate as a result of these effects. Cyclodextrin has been positioned as an effective facilitating and usable excipients. This article discusses the widespread use of Cyclodextrin as excipients in drug formulations as well as recent Cyclodextrin developments.